2013
DOI: 10.1111/and.12187
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid protects erectile function in diabetic rats

Abstract: We aimed to evaluate the effect of acetylsalicylic acid (ASA) treatment on diabetes-induced erectile dysfunction. Adult male Sprague-Dawley rats were divided into four groups as follows: (i) control (C), (ii) diabetic (D), (iii) ASA-treated control (C+ASA) and (iv) ASA-treated diabetic (D+ASA) groups. In groups 2 and 4, diabetes was induced by injection of 35 mg kg(-1) streptozotocin. ASA (100 mg kg(-1) day(-1) , orally) was administrated to rats in groups 3 and 4 for 8 weeks. Both intracavernosal pressure (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 27 publications
0
28
0
2
Order By: Relevance
“…There have been conflicting results on the contractile responses of diabetic erectile tissue. 35,36 The contractile response has been reported to be lower 37,38 or unchanged 39,40 in diabetic rats. The reason for this difference could be the methodology used to measure the contractile response to Phe and EFS.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting results on the contractile responses of diabetic erectile tissue. 35,36 The contractile response has been reported to be lower 37,38 or unchanged 39,40 in diabetic rats. The reason for this difference could be the methodology used to measure the contractile response to Phe and EFS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Indications for NSAID administration are multiple, ranging from fever, acute or chronic pain, biliary or ureteral colic, and rheumatologic disorders to dysmenorrhea. [ 4 ] Meanwhile, apart from the protective role against stroke, thrombosis, and cancer, [ 4 , 12 , 28 ] the most popular aspirin has been regarded as the primary CVD prophylaxis, [ 4 , 12 , 28 ] which is the result of COX-1 inhibition and endothelium-dependent arterial relaxation. [ 28 , 29 ] More non-aspirin NSAIDs are also studied to test their potential roles in preventing CVD and acute myocardial infarction.…”
Section: Nsaidsmentioning
confidence: 99%
“…In ex vivo studies, aspirin has been shown to improve the arterial blood flow and to prevent hypercoagulation in the penis of the Chacma baboon during erection (Bornman, Franz, Jacobs, & Du Plessis, ). In diabetic rats, aspirin has been found to normalise the diminished mean intracavernosal pressure/mean arterial blood pressure ratio required to recuperate erectile function (Hafez et al., ). Studies in vitro show that aspirin can protect and restore ED, and this has been indicated by an improved relaxation response to acetylcholine, improvements in electrical field stimulation and the presence of sodium nitroprusside in corpus cavernosum strips (Hafez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic rats, aspirin has been found to normalise the diminished mean intracavernosal pressure/mean arterial blood pressure ratio required to recuperate erectile function (Hafez et al., ). Studies in vitro show that aspirin can protect and restore ED, and this has been indicated by an improved relaxation response to acetylcholine, improvements in electrical field stimulation and the presence of sodium nitroprusside in corpus cavernosum strips (Hafez et al., ). These vasoactive responses are mediated through local generation of nitric oxide, acetylation of endothelial nitric oxide synthetase, or increased levels of neuronal nitric oxide synthase in penile vessels, and all are independent of the levels of cyclooxygenase I or II or the intracellular or extracellular calcium level.…”
Section: Discussionmentioning
confidence: 99%